The Effect of Coffee on Spermatozoa Motility and Morphology of BALB/c Mice Exposed to Electric Mosquito Repellent - Mulyono, Yehezkiel Andrew; Prihasna, Septika Nuri; Wibowo, Dhega Anindita; Johan, Andrew; Ngestiningsih, Dwi; Juniarto, Achmad Zulfa (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2021)
Introduction: Electric mosquito repellent which contains d-allethrin producing free radicals, affects the quality of sperm motility and morphology. Antioxidants contained in coffee can counteract the free radicals in the body. Objective: To evaluate the effect of coffee on sperm motility and morphology of BALB/c mice exposed to electric mosquito repellent. Methods: In this experimental study was conducted with post-test only control group design, 24 BALB/c mice randomized into 4 groups. The negative control group was a group without treatment. The positive control group was exposed to electric mosquito repellent. Group P1 and P2 were exposed to electric mosquito and given the coffee solutions with the doses respectively 52 mg/0.5 mL and 78 mg/0.5 mL. The treatment was given for 35 days. On the 36th day, all mice were terminated and their sperm motility and morphology were examined. The data were then analyzed with the non-parametric test of Kruskal-Wallis. Differences were considered significant when the value of p<0.05 with confidence interval 95%.Results: The result of pairwise comparison test progressive sperm motility shows that there was a significant difference between positive control group with P2 group (p=0.006), positive control group with negative control group (p<0.001), and P1 group with negative control group (p=0.004). The result of Kruskal-Wallis test for sperm morphology shows that there was no significant difference between those four groups (p=0.885).Conclusion: Coffee can significantly increase the sperm motility but didn’t significantly increase the normal sperm morphology percentage of BALB/c mice exposed by electric mosquito repellent.